An Assessment of Essential Palliative Care Health Services in Namibia - Niikondo, Hileni Nangulohi; Mitonga, Kabwebwe Honoré (International Journal For Research In Health Sciences And Nursing, 2018)
The rise in prevalence of health conditions such as Non-Communicable Diseases particularly in most African countries reveals the significant need for introducing the Palliative Care services in a National Health System. The study aimed at determining the proportion of physical infrastructure and resources available for the provision of palliative care services to patients in need at the healthcare facilities of Ohangwena and Khomas regions, Namibia. Although the healthcare facilities indicated having sufficient equipment, most (66.7%) displayed lack of mobility equipment, such as patient hoist, wheel chairs and pain medications such as morphine. There was statistical significant difference in the proportion of morphine availability between peripheral region and central region healthcare facilities (p<0.005. The study concluded that while the healthcare facilities showed some available resources, crucial resources such as patient hoist and morphine medications are needed to improve the quality of holistic palliative care services in the Namibian public health system.